DESIGN AND DEVELOPMENT OF EDUCATIONAL DEVICES PLANT DIVERSITY INQUIRY GUIDED BY PODCASTS AND GOOGLE CLASSROOM TO INFLUENCE STUDENTS' SCIENTIFIC WORK ABILITIES AND CRITICAL THINKING - Witia Ardipeni; Ibrohim Ibrohim (Universitas Muhammadiyah Semarang, 2021)
The globe is currently in the twenty-first century. The 21st century requires 4C (Critical Thinking, Communication, Creative Thinking, and Collaboration) abilities, as well as scientific work. In an effort to prepare students for the difficulties of the twenty-first century, the Indonesian government developed the 2013 curriculum via a scientific method. Inquiry in line with the 2013 curriculum. Due to the pandemic Covid-19, educational activities must be conducted online. Online education necessitates creativity in learning activities. Podcasts may be utilized as a kind of educational material that can be accessed from any location and at any time. The objectives of this research and development are to: (1) design and develop plant diversity-based inquiry-based podcasts and Google Classroom; and (2) influence the scientific work abilities and critical thinking of class X students at Malang's State Senior High School 8. (SMAN 8 Malang). The improvement of student abilities may be determined by comparing the pretest value to the posttest value using n-gain. Addie from Branch was utilized as the development model. Instruments for data collection include validation sheets, questionnaires designed to assess learning, student response surveys, and pretest and posttest questions. The research was performed at Malang's State Senior High School 8 (SMAN 8 Malang), using students from class X MIA-4 as subjects. The validation results for the design and learning tools generated are 82.4 valid categories, 89 and 82.3 highly practical categories, and 0.06 for the efficacy of scientific work students' skills 0, 2 and critical thinking.Keywords: Draft learning, guided inquiry, scientific work, critical thinking